USING ENGLISH SONGS IN TEACHING ENGLISH FOR YOUNG LEARNERS (EYLs) - Mudra, Heri (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri (IAIN) Kerinci, 2016)
English songs can be used for teaching English skills to young learners. The advantage of the English songs is they are authentic materials which represent real, native cultures. The way of teaching English by using the songs is by employing several steps of teaching namely pre-listening, whilst-listening, and post-listening activities.